2014
DOI: 10.2306/scienceasia1513-1874.2014.40.048
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis and inheritance of fertility-restorer genes in rice

Abstract: Three-line hybrid rice technology can increase rice yield. This study aims to identify restorers and maintainers, to estimate heterosis of hybrid rice, and to identify fertility-restorer genes of F2 populations. The analysis of 31 test crosses revealed 6 restorers and 9 maintainers based on pollen fertility. The estimation of heterosis to select superior genotypes was conducted on 12 hybrids resulting from crosses between 6 restorers and 2 male sterile lines. The results show that two hybrids had a high hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
(10 reference statements)
2
6
0
Order By: Relevance
“…This suggests that the restorer line used carried two independent dominant fertility restoring genes, and one of the two genes had a duplicate effect that showed higher expression than the other gene and it alone could restore fertility. The findings are in line with those reported by Sattari et al (2008), Seesang et al (2014) and Hasan et al (2015) who found the duplicate dominant epistatic gene action at the fertility restoration inheritance of WA and Gambiaca CMS.…”
Section: Pollen Fertility Analysis In F 2 Populationssupporting
confidence: 92%
See 2 more Smart Citations
“…This suggests that the restorer line used carried two independent dominant fertility restoring genes, and one of the two genes had a duplicate effect that showed higher expression than the other gene and it alone could restore fertility. The findings are in line with those reported by Sattari et al (2008), Seesang et al (2014) and Hasan et al (2015) who found the duplicate dominant epistatic gene action at the fertility restoration inheritance of WA and Gambiaca CMS.…”
Section: Pollen Fertility Analysis In F 2 Populationssupporting
confidence: 92%
“…Pollen fertility data in F 2 populations were classified into two groups, i.e. fertile (FF + PF + PS) and sterile (FS) (Seesang et al 2014).…”
Section: Evaluation Of Pollen and Spikelet Fertility In F 1 And F 2 Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterosis breeding is a principal genetic appliance that can facilitate yield enhancement by 30-40% and contributes to raising the desirable qualitative and quantitative traits in cultivated plants (Srivastava, 2000). Various degree of heterosis and heterobeltiosis on cultivars and elite lines of rice were observed by Nevame et al (2012); Sadimantara et al (2014); and Seesang et al (2014) for some agronomic and yield characters. The objectives of this study were to evaluate heterosis and heterobeltiosis of agronomic traits in Thai upland rice for identifying and selecting the favorable parental lines or cross combinations for developing high yielding upland rice varieties.…”
Section: Introductionmentioning
confidence: 88%
“…Based on fertility status, plants are classified into two groups, fertile and sterile. IR80151A was developed by IRRI and was used as female parent for three-line hybrid rice system in Thailand [36]. The results revealed that two dominant complementary genes with epistasis controlled the fertility-restorer gene of wild-abortive cytoplasmic male sterility system (WA-CMS).…”
Section: Genetic Control Of Fertility Restorationmentioning
confidence: 99%